Adhesion performance study of a novel microstructured stamp for micro-transfer printing. Issue 19 (26th April 2021) - Liang, Cunman; Wang, Fujun; Huo, Zhichen; Shi, Beichao; Tian, Yanling; Zhang, Dawei
Abstract : We propose a novel microstructured stamp for micro-transfer printing, which consists of a microchamber and microchannels. Abstract : Micro-transfer printing is an effective method that enables the integration of micro-scale heterogeneous materials for flexible electronics. As the key component of micro-transfer printing equipment, the stamp is adopted to pick up and print microdevices due to its reversible and controllable adhesion. In this paper, we propose a novel microstructured stamp based on the bionic theory, which consists of a microchamber and four microchannels. A theoretical model about the pressure change of the gas in the microchamber is established and the effects of compression distance and pull-up velocity on the pull-off force of the stamp are investigated. The performance test results show that the pull-off force of the stamp can be controlled by both the compression distance and the pull-up velocity. Finally, micro-transfer printing operations of microdevices with different sizes, shapes and materials are realized based on the proposed microstructured stamp. The results show that the proposed microstructured stamp exhibits good performance in the transfer printing of microdevices, and provides a new way for the design of microstructured stamps for micro-transfer printing without an extra excitation system.